Respuestas

¡La mejor respuesta!
  • Usuario de Brainly
2014-01-16T20:19:27+01:00
Recuerda: 
x² - 1 = (x + 1)* (x - 1)

 \frac{3}{x +  1}- \frac{2}{x^2-1} +\frac{x}{x-1}=

Pasamos a común denominador:

 \frac{3*(x-1)}{(x + 1)* (x - 1)}- \frac{2}{x^2-1} +\frac{x*(x+1)}{(x + 1)* (x - 1)}=

 \frac{3x-3}{x^2-1}- \frac{2}{x^2-1} +\frac{x^2+x}{x^2-1}=

 \frac{3x-3-2+x^2+x}{x^2-1}=

3x-3-2+x^2+x=x^2-1

3x-3-2+x^2+x-x^2+1=0

3x-3-2+x+1=0

4x-3-2+1=0

4x-4 = 0

4x = 4

x= \frac{4}{4}

x=1

Solución: 
x = 1